A two-step pH control method to remove divalent metals from near-neutral mining and metallurgical waste drainages by inducing the formation of layered double hydroxide. (1st October 2020) - Frau, Franco; Atzori, Roberta; Ardau, Carla; Medas, Daniela; Podda, Francesca; Dore, Elisabetta; Idini, Alfredo; Tempesta, Gioacchino; Agrosì, Giovanna
Abstract: A neutral M 2+ -rich and M 3+ -poor (M = metal) metallurgical waste drainage was used to test a metal removal method based on the precipitation of layered double hydroxide (LDH). The LDH precipitation was induced by adding a salt of Al 3+ (trivalent metal missing in the drainage) and maintaining or restoring the pH to a circum-neutral value. The precipitates were characterized by chemical analysis, XRD, ESEM, HRTEM and XAS. The main parameter controlling the removal of metals and the type of precipitate appeared to be the pH. As a function of pH variation during the experiments, analyses of precipitates and solutions showed either the formation of poor crystalline LDH combined with very high removal of Zn, Ni and Pb (92–100%), more variable removal of Mn (46–98%) and less Cd (33–40%), or the formation of more crystalline LDH combined with lower removal of Zn (62%), Mn (43%), Ni (88%), Pb (64%) and especially Cd (1%). The different metal removal efficiency in the two cases is only indirectly due to the different LDH crystallinity, and it is clearly affected by the following factors: 1) the two pH steps of the method; 2) the direction of pH variation within each step. In particular, the highest removal of metals is obtained when the first pH step goes towards acidic conditions, as a consequence of Al salt addition, and precipitation of a quasi-amorphous hydrated hydroxysulfate of Al (probably a precursor of felsӧbányaite Al4 (SO4 )(OH)10 · 4H2 O) occurs. This first acidic pH step removes little or no metals (just 0–3%) but it is essential so that the second pH step towards slightly alkaline conditions, as a consequence of NaOH addition, can be highly efficient in removing divalent metals as the quasi-amorphous hydrated hydroxysulfate of Al gradually turns into an LDH incorporating Zn, Mg and other metals. On the contrary, when both pH steps remain in the neutral-alkaline range, only LDH precipitation occurs and a lower metal removal is observed. These results encourage further investigations on the removal of metals by inducing LDH precipitation as a simple and effective method for the treatment of circum-neutral polluted drainages. Highlights: Environmental issue: near-neutral mining drainages with high contents of divalent metals but very low of trivalent ones. Challenge: find a frugal method (i.e. simple, effective, low-cost) to treat near-neutral metal-polluted drainages. Method: metal removal by inducing LDH precipitation by addition of a trivalent metal (e.g., Al 3+ ) missing in the drainage. Result: formation of an amorphous Al-bearing phase at acidic pH as the main constraint for a high metal removal efficiency. Mechanism: while increasing pH, the amorphous Al-bearing phase gradually transforms into LDH, uptaking divalent metals.